EvaluationBacterial Contamination Levels of Imported and Locally Produced Chicken Meat Rollingin Al-Bayda City Markets (Al-Farooq Journal of Sciences, 2026)
This study aimed to evaluate the microbiological safety of chicken meat marketed in Al-Bayda City, Libya, by analyzing samples of both locally produced and imported chicken for the presence of  Escherichia coli ( E. coli ) and determining the total viable count (TVC).The results indicated that all samples were within the permissible limits according to international standards, confirming the overall microbiological safety of the meat. However, higher contamination levels were observed in locally produced chicken compared to imported samples.For imported chicken, the mean TVC values were 2.7 log CFU/g in breast meat and 3.6 log CFU/g in thigh meat, while  E. coli  counts ranged from 1.8 log CFU/g in breast to 2.3 log CFU/g in thigh samples, all within internationally accepted limits (6–7 log CFU/g for TVC and
Keywords: Safety, E. coli , Bacteria, Chicken, Standards, Microbiology